(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
The area of study is situated in the Nige r Delta . The current study is concerned with the analysis of magnetic and gravity data aiming to evaluate the subsurface structure of the basement rocks . The aeromagnetic and gravity methods of prospecting give an effective presentation of the subsurface structures . The aeromagnetic data was corrected and represented by total aeromagnetic intensity map then was reduced to the north magnetic pole . The corrected gravity data is represented by Bouguer anomaly map. The ﬁltering techniques were applied to the corrected aeromagnetic and gravity maps to obtain the residual component caused by local structures and anomalies bodies . The integration of radially power spectrum was applied on both magnetic and gravity to estimate the depths of the shallow sources and the deep sources . The equivalent depths of the isolated short wavelength anomalies are 0.5 km and 0.4 km, and the depths of the long wavelength anomalies are 3.5 and 3 km for the magnetic and gravity data, respectively. The Euler deconvolution and 3-D modeling were applied to magnetic and grav- itydata . The 3-D Euler deconvolution is used not only to delineate major subsurface structures but also to determine the structural indices of them as well as the average depth of the magnetic and gravity sources . The calculated structural indices show that the area is mainly affected by contacts/thin sheet and the esti- mated depth of magnetic and gravity sources ranged between 500 m and 2000 m, also the 3-D Euler deconvolution showed that the area was affected by different fault trends such as NNE-SSW, NW-SE and E-W trends . The results of 3-D magnetic and gravity interpretation revealed that the depth of base- ment was ranging from 2500 m to 3000 m .The main tectonic deformations of the area of study have NNE-SSW, NW-SE and E-W trends .